Professor Lech Bieganowski (1940–2017) – meritorius ophthalmologist and outstanding expert of history of ophthalmology - Grzybowski, Andrzej; Kazało, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Lech Bieganowski was born on 7 June 1940. In 1964 he became a medical doctor and began working at the Ophthalmological Ward of the Municipal Hospital in Toruń. He earned his PhD degree in medicine in 1977 at the Medical Academy in Gdansk. The same year he became the Chief Doctor of the Ophthalmological Ward of Regional Hospital in Torun. He held this position till the very end of his professional career. He earned his post-doctoral degree in 2003 at the Medical Academy in Szczecin on the basis of the dissertation Anatomy of the eye and the manner of image formation according to medieval scholars: Ibn al-Haytham and Witelo. Professor Lech Bieganowski was an author and a co-author of over eighty works published in Polish and foreign scientific journals and presented at scientific congresses. He had a wide range of interests; it concerned the surgery of cataract, the surgery of eyelids, pediatric ophthalmology and squint treatment, imaging technologies in ophthalmology, optometry and the history of medicine, ophthalmology and optics in particular. Lech Bieganowski took part in the works of a team of scholars gathered around the Institute of Physics of the Nicholas Copernicus University in Torun. The team took the initiative to translate Witelon’s work Perspectiva from Latin into Polish and to present Witelon, the first Polish scholar of international recognition living in the 13th century in Lower Silesia. Lech Bieganowski was an outstanding expert on the history of ophthalmology. He was an author of the book published in 2014 Outline of the history of ophthalmology in the Mediterranean culture comprising ancient times, intended as the first volume in the series. He began working on the second volume. Lech Bieganowski died on 22 March 2017.